Continuous liquid‐suction catheter attachment for endoscope reduces volume of liquid reflux to the mouth in esophageal endoscopic submucosal dissection. Issue 5 (4th April 2019) - Hatta, Waku; Koike, Tomoyuki; Okata, Hideki; Hanzawa, Takashi; Saito, Masahiro; Kondo, Yutaka; Ara, Nobuyuki; Asanuma, Kiyotaka; Uno, Kaname; Asano, Naoki; Imatani, Akira; Iijima, Katsunori; et al.
Abstract : Background and Aim: Pooling of liquid in the esophageal lumen can worsen the field of vision and cause liquid reflux to the mouth, which leads to aspiration pneumonia, in esophageal endoscopic submucosal dissection (ESD). We developed a continuous liquid‐suction catheter attachment for the endoscope (CLCA) that has multiple tiny holes and can suction the liquid without causing mucosal injury. Thus, we aim to show the efficacy of CLCA in esophageal ESD. Methods: This was a single‐blinded, randomized controlled trial involving patients with superficial esophageal cancer. The enrolled patients were randomly assigned to the conventional ESD (C‐ESD) or ESD with CLCA (CLCA‐ESD) groups. Primary endpoint was volume of liquid reflux to the mouth during the ESD procedure. Secondary endpoints were incidence of aspiration pneumonia and procedure time. Results: Fifty patients were enrolled in this trial. Volume of liquid reflux to the mouth was significantly lower in the CLCA‐ESD group than in the C‐ESD group (mean: 10 vs 73 mL, P  =   0.010). Furthermore, the incidence of aspiration pneumonia on computed tomography (CT) scan between the two groups was also significantly different (4.0% vs 32.0%, P  =   0.023), although no significant difference was observed through chest radiography. In addition, procedure time tended to be shorter in the CLCA‐ESD group ( P  =   0.054). Conclusion: This study first showed that use of CLCA in esophageal ESD reduced the volume of liquid reflux to the mouth and contributed to decreased incidence of aspiration pneumonia on CT scan (UMIN000018167).